Professional Self-Concept Model on Working Productivity of Clinical Nurses - Kusnanto Kusnanto; I Gede Juanamasta; Slamet Riyadi Yuwono; Yulastri Arif; Kadek Ayu Erika; Hidayat Arifin (Journal of Global Pharma Technology, 2020)
Introduction: The nurses' professional self-concept is concerned with how individuals perceive themselves as professionals and in nursing is about what nurses feel about themselves as nurses. The purpose of this study is to develop a professional self-concept model on the productivity of the nurse's work. Methods: An explanatory design with cross-sectional approach. Samples were 311 nurses in inpatient room with simple random sampling. Data analysis using Partial Least. Organizational aspects (0.4397). Results: Characteristics of the work (0.1978) and the organizational environment (0.5391) were affects the nurses' professional self-concept. The self-concept of professional nurses affects work productivity (0.4953). Conclusion: Organizational characteristics, work characteristics, and organizational environment have a relationship with professional self-concept of nurses. Furthermore, the self-concept of professional nurses has a relationship and can enhance nurse work productivity. Professional self-concept nurses form a professional identity in nurses who increase nurse productivity at work.